Análise do trabalho padronizado sobre a ótica da ergonomia: um estudo de caso em uma indústria de componentes para refrigeração. - Balsadi, Daniela (Universidade Federal de São Carlos, 2024)
With the development of advanced technologies and increasingly competitive and streamlined production processes, Lean Manufacturing (LM) and ergonomics have become ever more closely integrated in process improvement, yielding transformative effects on work design and organization. In this context, standardized work, within the LM framework is one of the tools that can be employed to reduce process times and eliminate waste, particularly waste related to unnecessary movement. To better understand the potential of this integration, a case study was conducted in which standardized work was implemented at the workstation exhibiting the longest cycle time, in order to assess its possible positive impacts (improvements in task execution and comfort, reduction in movement range, decreased fatigue, job enrichment, creative thinking, autonomy, enhanced well-being, and reduction or elimination of waste) as well as potential negative effects (reduced cycle time flexibility, task rigidity, increased stress, heightened pressure on workers, and greater workload). The research took place at a metalworking company located in the interior of São Paulo state. During the analysis of the targeted operation, a lack of task standardization became evident. Consequently, a standardized work method was developed and implemented, seeking a comfortable and efficient procedure in which workers could actively participate in the design, implementation, and validation of the new methods. To quantify and define work elements, a time-and-motion study was performed using the Method Time Measurement (MTM) tool; to quantify biomechanical risks, Suzanne Rodgers’s checklist was applied. The study aimed to establish safe and reliable work methods by considering both the actual activity and its inherent variabilities. In order to determine the optimal method, participatory ergonomics techniques were employed, and questionnaires were administered to assess workers’ perceptions before and after the introduction of standardized work and ergonomic improvements. Within the scope of the case study, it was found that, following implementation, workers reported higher job satisfaction, cycle-time improvements, reduced biomechanical demands (fatigue), and enhanced productivity (more streamlined and optimized processes). Despite the shorter process times and introduction of standardized methods, workers felt more confident and comfortable in performing their tasks. Overall, the integration of Lean Manufacturing tools with ergonomic principles demonstrates significant potential for the development of operational processes that are safer, leaner, more efficient, and conducive to preserving workers’ health.
Ergonomic analysis of standardized work: a case study in the refrigeration components industry.
Keywords: Lean manufacturing; Ergonomics; Human factors; Trabalho padronizado; Standardized work; Ergonomia; Fatores humanos; Produção enxuta; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::PROCESSOS DE TRABALHO; 3. Saúde e Bem-Estar